Pendidikan Islam Pada Masa Awal di Indonesia - Harlinda; Bahaking Rama; Muhammad Yahdi (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Education in Indonesia has been running on the basis of a duality between general education and religious education, resulting in a separation between secular knowledge and religious knowledge. This has been the case since the colonial Dutch government introduced a secular education system. This journal article will discuss the history of the development of Islamic education in Indonesia, Islamic educational institutions that emerged in the early period of Indonesia, and the progress of Islamic education in Indonesia. This research is entirely literature-based (Library Research), where data is gathered through library resources such as books. This type of research is qualitative in nature, employing the method of historical research, specifically heuristic and data collection techniques through literature review. The data processing in this study involves: (1) Inductive approach, which entails interpreting and analyzing specific data to draw general understandings and conclusions; (2) Deductive approach, which involves interpreting and analyzing general data to derive specific understandings and conclusions; (3) Comparative approach, which entails comparing one set of data with another to draw conclusions. The results of this research indicate that since the early development of Islam, education has been given top priority by the Muslim community in Indonesia due to its significant importance. The interest in Islamization has motivated Muslims to carry out Islamic teachings, even within a very simple system, where teaching is conducted through halaqah sessions held in places of worship such as mosques, prayer rooms, and even in the homes of religious scholars. In the initial stage, Islamic education took place informally. Many Muballighs (Islamic preachers) provided exemplary examples and demonstrated noble character, which attracted the communities they visited to embrace Islam. Some of the early Islamic educational institutions that emerged in Indonesia were mosques and langgars, pesantren (Islamic boarding schools), meunasah, rangkang, and surau